Dewatering characteristics of sludge conditioned by surfactant with bioleaching pretreatment - Liu, Changgeng; Zhang, Xuefeng; Wu, Bin; Chen, Xiao’e; Xie, Sicai (Water and environment journal : WEJ, 2019)
In view of the merits of bioleaching and surfactant for sludge treatment, the possibility of surfactant with bioleaching pretreatment applied to improve sludge dewaterability was investigated in this work. The results showed that cetyl trimethyl ammonium chloride (CTAC) with bioleaching pretreatment was highly efficient in dewatering sludge. The optimal CTAC dosage and bioleaching pH for this combination were 120 mg/g (dry solids) and 3.55, respectively, under which the water content of filtrated cake was 68.94% and the specific resistance to filtration was 0.12 × 1013 m/kg with a reduction of 94.92%. Although CTAC and bioleaching both had positive effects on sludge dewatering, their combination was more efficient. The significant enhancement of sludge dewaterability was mainly contributed from the breakage and charge neutralization of sludge flocs, and the release of extracellular polymeric substances (EPS). In addition, the positive correlation between supernatant EPS concentration and sludge dewaterability was observed under experimental conditions.